Questioning the UN's Immunity in the Dutch Courts: Unresolved Issues in the Mothers of Srebrenica Litigation - Benjamin E. Brockman-Hawe (Washington University Global Studies Law Review, 2011)
The Article discusses the court case Mothers of Srebrenica v. the Netherlands & the United Nations regarding the mandate of the United Nations on the prevention of the 1995 attacks against the Muslims of Bosnia at Srebrenica and the failure of the Dutch troops to act upon the situation. The decision of the International Court of Justice and former Yugoslavia's International Criminal Tribunal regarding the case is also presented.
Keywords: Actions & amp; defenses (Law); Muslims – Bosnia & amp; Hercegovina; Armored troops; International Court of Justice; International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991